2014
DOI: 10.1123/jsm.2013-0136
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Consequences of the Perceived Social Impact of a Sport Event

Abstract: This study investigates the determinants and consequences of the perceived social impact of a sport event by analyzing data obtained from 458 local attendees of the 2012 FedEx St. Jude Classic. Results show that a sport event generates a higher level of social impact for local attendees if they feel a greater sense of social camaraderie at the event and/or perceive a higher level of the social responsibility of the event. In turn, the creation of social impact leads to greater business returns, such that local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 52 publications
10
119
0
6
Order By: Relevance
“…Our observations of the new relationships continuing to evolve in the off-season and permeating into broader areas of life (e.g., business and family) supports the notion that relationships provide enduring benefits (Wann, 2006c) and highlights the significance of relationships as a well-being domain (Seligman, 2011). The importance of building relationships with others has been reported extensively in participatory settings (Coghlan & Filo, 2013) as well as in spectator research demonstrating how sport entities can act as a social catalyst facilitating the development of connections with specific communities and likeminded individuals (Gibson et al, 2002;Harrolle, et al, 2010;Heere, James, Yoshida, & Scremin, 2011;Inoue & Havard, 2014;Katz & Heere, 2013;Lock & Funk, in press;Trail et al, 2000Trail et al, , 2005Trail et al, 2003;Wann & Weaver, 2009). Perhaps most importantly, the results support Wann's (2006c) TISPH model and provide insights into the specific actions that enhance social interaction and social-psychological health (Wann & Weaver, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations of the new relationships continuing to evolve in the off-season and permeating into broader areas of life (e.g., business and family) supports the notion that relationships provide enduring benefits (Wann, 2006c) and highlights the significance of relationships as a well-being domain (Seligman, 2011). The importance of building relationships with others has been reported extensively in participatory settings (Coghlan & Filo, 2013) as well as in spectator research demonstrating how sport entities can act as a social catalyst facilitating the development of connections with specific communities and likeminded individuals (Gibson et al, 2002;Harrolle, et al, 2010;Heere, James, Yoshida, & Scremin, 2011;Inoue & Havard, 2014;Katz & Heere, 2013;Lock & Funk, in press;Trail et al, 2000Trail et al, , 2005Trail et al, 2003;Wann & Weaver, 2009). Perhaps most importantly, the results support Wann's (2006c) TISPH model and provide insights into the specific actions that enhance social interaction and social-psychological health (Wann & Weaver, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Research has illustrated that relationships can be both an antecedent and an outcome of sport spectating, demonstrating the ongoing interaction between sport consumption and the connections built through spectating (Wann, 2006c). Research has demonstrated that a heightened sense of camaraderie at an event can influence perceptions of the social impact of the event and the purchasing behaviour of attendees in relation to the event and the event sponsor's products (Inoue & Havard, 2014).…”
Section: Relationshipsmentioning
confidence: 99%
“…A review of extant literature suggests that there are two types of cause-related sport sponsorship (Fortunato, 2009;Inoue & Havard, 2014;Irwin et al, 2003Irwin et al, , 2010. The first type is a firm's sponsorship of a cause-related sport event, a spectator sport event that is directly linked to a specific cause and operates with the purpose of raising funds for a specific benefactor (Inoue & Havard, 2014). The FESJC is an example of a cause-related sport event because it is directly related to a specific cause (i.e., pediatric cancer and other catastrophic illnesses) and raises money and awareness for its benefactor, St. Jude.…”
Section: Cause-related Sport Sponsorshipmentioning
confidence: 99%
“…Because of its cause affiliation, employees' reaction to cause-related sport sponsorship may be different from their reaction to regular sport sponsorship. Indeed, research on consumers suggests that the cause affiliation, rather than the sport affiliation, of cause-related sport sponsorship predominantly determines the consumer evaluation of this category of sponsorship (Irwin et al, 2003(Irwin et al, , 2010Lee & Ferreira, 2013), although some evidence still points to the opposite conclusion (Inoue & Havard, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…O contexto social e cultural tem sido apontado na literatura como sendo importante na avaliação da qualidade dos eventos (AU, 1999, AGARWAL;MALHORTA;BOLTON, 2010). Em linha com esta ideia, estudos têm demonstrado a importância de se identificar fatores que influenciam a percepção da qualidade do evento para os consumidores (PORTER;FLETCHER, 2008, INOUE;HAVARD, 2014).…”
Section: Introductionunclassified